Protein phosphatase 2A (PP2A) inhibitor CIP2A indicates resistance to radiotherapy in rectal cancer - Eva-Maria Birkman; Adam Elzagheid; Terhi Jokilehto; Tuulia Avoranta; Eija Korkeila; Jarmo Kulmala; Kari Syrjänen; Jukka Westermarck; Jari Sundström (John Wiley & Sons, Ltd, 2025)
Preoperative (chemo)radiotherapy, (C)RT, is an essential part of the treatment of rectal cancer patients, but tumor response to this therapy among patients is variable. Thus far, there are no clinical biomarkers that could be used to predict response to (C)RT or to stratify patients into different preoperative treatment groups according to their prognosis. Overexpression of cancerous inhibitor of protein phosphatase 2A (CIP2A) has been demonstrated in several cancers and is frequently associated with reduced survival. Recently, high CIP2A expression has also been indicated to contribute to radioresistance in head and neck squamous cell carcinoma, but few studies have examined the connection between CIP2A and radiation response regarding other malignancies. We have evaluated CIP2A protein expression levels in relation to tumor regression after preoperative (C)RT and survival of rectal adenocarcinoma patients. The effects of CIP2A knockdown by siRNA on cell survival were further investigated in colorectal cancer cells exposed to radiation. Patients with low-CIP2A-expressing tumors had more frequently moderate or excellent response to long-course (C)RT than patients with high-CIP2A-expressing tumors. They also had higher 36-month disease-specific survival (DSS) rate in categorical analysis. In the multivariate analysis, low CIP2A expression level remained as an independent predictive factor for increased DSS. Suppression of CIP2A transcription by siRNA was found to sensitize colorectal cancer cells to irradiation and decrease their survival in vitro. In conclusion, these results suggest that by contributing to radiosensitivity of cancer cells, low CIP2A protein expression level associates with a favorable response to long-course (C)RT in rectal cancer patients.